Maturity Level Analysis of FT ULM Service System Using The Cobit 2019 Framework - Muhammad Asriannoor (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2024)
Effective use of Information Technology (IT) is a key factor in improving the quality of educational services offered by the Faculty of Engineering, Lambung Mangkurat University (FT ULM). To achieve this goal, FT ULM is committed to continuously improving its performance and services in IT governance. This research focuses on measuring the maturity level of IT governance in FT ULM's service system, particularly in the service aspect. The objective is to analyze the maturity level of FT ULM's service system using the COBIT 2019 framework. The evaluation is conducted to identify the gap between the current and desired conditions, and provide recommendations for improving IT governance. The methods employed include literature review, data collection through questionnaires and interviews, and data analysis using the COBIT 2019 framework. Data collection is focused on relevant domains, such as Build, Acquire, and Implement (BAI), Align, Plan, and Organize (APO), Deliver, Service, and Support (DSS), and Evaluate, Direct, and Monitor (EDM). The research results indicate that the average maturity level is at Level 3 (Established Process). There is a significant gap between the current and desired conditions, highlighting the need for improvement and enhancement in several aspects of IT governance. The recommendations provided include strengthening risk management, improving service system integration, and enhancing infrastructure and policies related to IT governance.